PATHWAY-2 and -3: Potassium-Sparing Diuretics Safe and Effective for Resistant Hypertension. Issue 28 (29th October 2015) - Zarifyan, Alla
PATHWAY-2 and PATHWAY-3 demonstrated that potassium-sparing diuretics are safe and effective for the treatment of hypertension. Spironolactone was significantly more effective in controlling resistant hypertension than doxazosin or bisoprolol, whereas the amiloride/HCTZ combination neutralized the undesirable changes in blood glucose and potassium while significantly lowering blood pressure.